Reputation Management in the Healthcare System and Its Impact for Sustainable Development - TASZHARGANOV, Sabit; TUREKULOVA, Dametken; NUKESHEVA, Anar; BEISENGALIYEV, Berik; ERKULOVA, Gulmira (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021DO - 10.14505/jemt.v12.1(49).04, 2021)
In a competitive environment, reputation is based on the authority of both an individual and social groups / organizations that have real power and are able to influence the decisions and actions of others. The degree and possibility of this power depend on how authoritative a given individual, group or organization is in solving certain problems. The relevance of the research topic is explained by the fact that in modern economic conditions, in a period of high competition, organizations, in order to increase competitiveness and prosperity in the market, pay great attention to reputation management, the quality of their work and the quality of customer service. This is especially true for the service sector, including the health care system and its impact for sustainable development.